Requirements for a maritime transition in line with the Paris Agreement - Sebastian Franz; Nicolas Campion; Sara Shapiro-Bengtsen; Rasmus Bramstoft; Dogan Keles; Marie Münster (iScience, 2022)
Summary: The shipping industry is a hard-to-abate sector in today’s society. Although past studies have looked at levels of carbon pricing, fuel savings, and the upscaling of green fuel availability separately, we combine these critical parameters for a green transition of the shipping industry to show what it takes to reach sectoral emissions reduction targets in line with the Paris Agreement. We utilize a least-cost optimization model drawing on data on, e.g., emissions with lifecycle elements and the costs of green fuel production. We find that reaching maritime reduction targets for a green transition requires high growth rates for green fuel availability, carbon pricing beyond 300EUR/tCO2eq, and at least 50% in fuel demand savings compared to today’s demand projection for 2050. The results show the importance of immediate climate action if maritime emissions reduction goals are to be achieved.